2013
DOI: 10.1186/1476-511x-12-7
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue arachidonic acid content is associated with the expression of 5-lipoxygenase in atherosclerotic plaques

Abstract: BackgroundThe content of arachidonic acid in adipose tissue is positively associated with the risk of myocardial infarction, whereas the content of eicosapentaenoic acid in adipose tissue has been reported to be negatively associated with the risk of myocardial infarction. Both arachidonic acid and eicosapentaenoic acid are substrates for the synthesis of pro-inflammatory leukotrienes and leukotrienes derived from eicosapentaenoic acid are generally much less potent. In this study we hypothesized that a high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Our previous study indicated that supplementation with 240 or 720 mg ARA per d did not significantly change plasma prostanoids, which are ARA metabolites produced through pathways other than leukotrienes, although plasma ARA levels increased ( 54 ) . Nielsen et al ( 55 ) reported that adipose tissue ARA was not correlated with either cys-LT formation in plaque or total body cys-LT formation in a cross-sectional study of subjects undergoing femoral thromboendarterectomy. Third, ARA metabolites other than cys-LT may decrease asthma risk.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study indicated that supplementation with 240 or 720 mg ARA per d did not significantly change plasma prostanoids, which are ARA metabolites produced through pathways other than leukotrienes, although plasma ARA levels increased ( 54 ) . Nielsen et al ( 55 ) reported that adipose tissue ARA was not correlated with either cys-LT formation in plaque or total body cys-LT formation in a cross-sectional study of subjects undergoing femoral thromboendarterectomy. Third, ARA metabolites other than cys-LT may decrease asthma risk.…”
Section: Discussionmentioning
confidence: 99%
“…This study included 48 participants (24 male/24 female) with symptomatic peripheral arterial disease undergoing femoral thrombendarterectomy as previously described ( 8 ) and 24 healthy controls (9 male/15 female, age >18 years). Exclusion criteria for the participants with femoral atherosclerosis were allergic asthma or rhinitis, systemic steroid treatment, chronic inflammatory diseases, acute coronary syndrome within the last 30 days, cancer, and inability to give informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Analyses of LTs and fatty acids in plaques have previously been described by Nielsen et al ( 8 ). Briefly, for LTB4 quantification, plaques removed during femoral artery thrombendarterectomy were cut into smaller pieces and stimulated with calciumionophore A23187 followed by a solid phase immunoassay ELISA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations